A randomised controlled trial of group cognitive behavioural therapy for perfectionism - Handley, Alicia; Egan, Sarah; Kane, Robert; Rees, Clare (Elsevier Ltd, 2015)
Perfectionism is associated with symptoms of anxiety disorders, eating disorders and mood disorders. Treatments targeting perfectionism may reduce the symptoms of these disorders (Egan, Wade, & Shafran, 2011). This study is the first randomised controlled trial to investigate the efficacy of group cognitive behavioural therapy (CBT) for perfectionism. Forty-two participants with elevated perfectionism and a range of anxiety, eating and mood disorders were randomised to group CBT for perfectionism or a waitlist control. The treatment group reported significantly greater pre-post reductions in perfectionism, symptoms of depression, eating disorders, social anxiety, anxiety sensitivity and rumination, as well as significantly greater pre-post increases in self-esteem and quality of life compared to the waitlist control group. The impact of treatment on most of these outcomes was mediated by pre-post change in perfectionism (Concern over Mistakes). Treatment gains were reliable and clinically significant, and were maintained at 6-month follow-up. Findings support group CBT for perfectionism being an efficacious treatment for perfectionism and related psychopathology, as well as increasing self-esteem and quality of life.